2020
DOI: 10.1111/tpj.14608
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis PIC30 encodes a major facilitator superfamily transporter responsible for the uptake of picolinate herbicides

Abstract: Picloram is an auxinic herbicide that is widely used for controlling broad leaf weeds. However, its mechanism of transport into plants is poorly understood. In a genetic screen for picloram resistance, we identified three Arabidopsis mutant alleles of PIC30 (PICLORAM RESISTANT30) that are specifically resistant to picolinates, but not to other auxins. PIC30 is a previously uncharacterized gene that encodes a major facilitator superfamily (MFS) transporter. Similar to most members of MFS, PIC30 contains 12 puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Statistical analysis showed that the ovule number per placenta of the wild-type and pin3 mutants at floral stages 9c-11 wasn't obviously increased under NAA treatment, implying that exogenous NAA did not efficiently enhance the auxin signal that is sufficient to promote ovule initiation, regardless of the presence of a functional PIN3 in the wild-type (S3A-S3C Fig) . Meanwhile, another auxin analogue, picloram was also applied to the wild-type and pin3 mutants. Picloram is transported into cells by a special native plasma membrane-bound influx carrier PIC30, a member of the major facilitator superfamily (MFS) [55,56]. Interestingly, the pistil length and ovule number of the wild-type and pin3 mutants were both significantly increased upon picloram treatment (Fig 5A -5C).…”
Section: Application Of Exogenous Auxin Analogue Affects Ovule Initia...mentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analysis showed that the ovule number per placenta of the wild-type and pin3 mutants at floral stages 9c-11 wasn't obviously increased under NAA treatment, implying that exogenous NAA did not efficiently enhance the auxin signal that is sufficient to promote ovule initiation, regardless of the presence of a functional PIN3 in the wild-type (S3A-S3C Fig) . Meanwhile, another auxin analogue, picloram was also applied to the wild-type and pin3 mutants. Picloram is transported into cells by a special native plasma membrane-bound influx carrier PIC30, a member of the major facilitator superfamily (MFS) [55,56]. Interestingly, the pistil length and ovule number of the wild-type and pin3 mutants were both significantly increased upon picloram treatment (Fig 5A -5C).…”
Section: Application Of Exogenous Auxin Analogue Affects Ovule Initia...mentioning
confidence: 99%
“…initiation even in the presence of NAA (S3 Fig) . By contrast, picloram, a synthetic auxin analogue, is absorbed rapidly by a special influx transporter PIC30 and accumulates in growing tissues [55,56]. Thus, the rapid uptake and accumulation of picloram, which is independent with PIN3, may be liable to enhance total auxin signaling and response (Fig 5D -5G).…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Four additional stress-related genes are also up-regulated under FeD conditions. These include Glyma.04G228300, a homolog of AtAPRR5 (At5g24470), which is involved in the SnRK pathway and regulates cytokinin [62]; Glyma.05G145000, a member of the multidrug resistance-associated protein family likely serving as a metal transporter in Arabidopsis (At3g13080) [60]; Glyma.05G169900, encodes a plantacyanin a copper-containing protein involved in tolerance to heavy metal stress tolerance in Arabidopsis (At2g02850) [63]; Glyma.10G276700, a major facilitator known to transport nitrate in Arabidopsis (At2g39210) [64], and Glyma.20G133200, a homolog of AtZAT10. In Arabidopsis, ZAT10 (At1g27730) is strongly induced by ABA and numerous abiotic stresses to provide enhanced stress tolerance [65].…”
Section: Degs Vigs_ev Response To Iron Treatmentmentioning
confidence: 99%